ChemInform Abstract: Increased Eu2+ Content and Codoping Mn2+ Induced Tunable Full‐Color Emitting Phosphor Ba1.55Ca0.45SiO4:Eu2+, Mn 2+. Issue 49 (9th December 2014) - Miao, Shihai; Xia, Zhiguo; Zhang, Jie; Liu, Quanlin
Abstract The new single‐phase white‐light emitting phosphor of title is prepared by solid state reaction of BaCO3, CaCO3, SiO2, MnCO3, and Eu2O3 (CO atmosphere, 1250 °C, 4 h).